IMPLEMENTATION OF SHARIA MAQASHID ON SUKUK BASED ON FATWA DSN-MUI/IX/2020 - Mahmudah, Siti Nur; Ghozali, Muhammad Lathoif; Ritonga, Iskandar (Universitas Islam Negeri Ar-Raniry, 2022)
Sukuk is an alternative option for government or corporate funding in the capital market for the sake of progressing the national economy. With the issuance of sukuk, the government or companies will get substantial funds. This is an attraction to help improve infrastructure development carried out by the government or companies. The approach taken in this research is a qualitative approach with library research type and is useful in collecting primary and secondary data sources in the form of documentation because it comes from several books, journals and other literature. The last step is data analysis through descriptive analysis method, namely data reduction, data display, and conclusion. The results of this study are the needs that can be met with the existence of sukuk, namely dharuriyah (mandatory needs), Hajiyyat (secondary needs), Tahsiniyyat (tertiary needs). This research was conducted with the aim of analyzing the benefits of issuing sukuk for a country from the perspective of maqashid sharia about sukuk